CaMKII, but not protein kinase A, regulates Rpt6 phosphorylation and proteasome activity during the formation of long-term memories - Jarome, Timothy J.; Kwapis, Janine L.; Ruenzel, Wendy; Helmstetter, Fred J. (Frontiers in Behavioral Neuroscience, 2013)
CaMKII and Protein Kinase A (PKA) are thought to be critical for synaptic plasticity and memory formation through their regulation of protein synthesis. Consistent with this, numerous studies have reported that CaMKII, PKA and protein synthesis are critical for long-term memory formation. Recently, we found that protein degradation through the ubiquitin-proteasome system is also critical for long-term memory formation in the amygdala. However, the mechanism by which ubiquitin-proteasome activity is regulated during memory formation and how protein degradation interacts with known intracellular signaling pathways important for learning remain unknown. Recently, evidence has emerged suggesting that both CaMKII and PKA are capable of regulating proteasome activity in vitro through the phosphorylation of proteasome regulatory subunit Rpt6 at Serine-120, though whether they regulate Rpt6 phosphorylation and proteasome function in vivo remains unknown. In the present study we demonstrate for the first time that fear conditioning transiently modifies a proteasome regulatory subunit and proteasome catalytic activity in the mammalian brain in a CaMKII-dependent manner. We found increases in the phosphorylation of proteasome ATPase subunit Rpt6 at Serine-120 and an enhancement in proteasome activity in the amygdala following fear conditioning. Pharmacological manipulation of CaMKII, but not PKA, in vivo significantly reduced both the learning-induced increase in Rpt6 Serine-120 phosphorylation and the increase in proteasome activity without directly affecting protein polyubiquitination levels. These results indicate a novel role for CaMKII in memory formation through its regulation of protein degradation and suggest that CaMKII regulates Rpt6 phosphorylation and proteasome function both in vitro and in vivo.